2008
DOI: 10.4321/s0210-48062008000600001
|View full text |Cite
|
Sign up to set email alerts
|

PSA y hK2 en el diagnóstico de cáncer de próstata

Abstract: RESUMENPSA Y hK2 EN EL DIAGNÓSTICO DE CÁNCER DE PRÓSTATA Los marcadores séricos de cáncer de próstata son ampliamente usados para la detección precoz de este cáncer, estadiaje tumoral y para la monitorización tras tratamiento curativo o paliativo. Desde su descubrimiento en 1979, el PSA ha sido el marcador de cáncer de próstata más importante. Sin embargo, el PSA de forma aislada no presenta una especificidad y sensibilidad adecuadas como para considerarlo un test idóneo en la detección precoz de cáncer de pró… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…HK2 can promote glucose metabolism to meet the energy needs of tumour cells, inhibit the accumulation of ROS and Ca 2+ in mitochondria, and increase the adaptability and survival of tumour cells [27] . Research has shown that HK2 is upregulated in various tumours and is involved in the occurrence and development of tumours (cervical cancer, liver cancer, prostate cancer) [28] , [29] , [30] . Sun et al [31] found that miR-615 was downregulated in OS tissue, and HK2 was a direct target of miR-615, with a negative correlation between the expression of the two.…”
Section: Target Molecules Affecting Glycometabolism In Os Developmentmentioning
confidence: 99%
“…HK2 can promote glucose metabolism to meet the energy needs of tumour cells, inhibit the accumulation of ROS and Ca 2+ in mitochondria, and increase the adaptability and survival of tumour cells [27] . Research has shown that HK2 is upregulated in various tumours and is involved in the occurrence and development of tumours (cervical cancer, liver cancer, prostate cancer) [28] , [29] , [30] . Sun et al [31] found that miR-615 was downregulated in OS tissue, and HK2 was a direct target of miR-615, with a negative correlation between the expression of the two.…”
Section: Target Molecules Affecting Glycometabolism In Os Developmentmentioning
confidence: 99%